Effect of Polyethyleneglycols (PEG) on Solubility of CoIII5,10,15,20-Tetra(4-carboxyphenyl)porphyrin and Methylimidazolyl Axial Complex at 298.2 K: Experiment and Modeling - Volkova,Tatyana V. (2016)
The solubility of CoIII 5,10,15,20-tetra(4-carboxyphenyl)porphyrin and axial complex with methylimidazole in the mixtures of triethyleneglycol-water and tetraethyleneglycol-water was measured in the whole range of polyethyleneglycols (PEG) fractions at 298.2 K using the isothermal saturation method. The composition of the mixture at which the maximal solubility was observed has been revealed. The cosolvent force of PEGs was quantified according to the linear logarithmic model proposed by Yalkowsky applied in the ranges (cosolvent volume fraction, f): 0 ≤ fPEG ≤ 0.24 in triethyleneglycol-water and 0 ≤ fPEG ≤ 0.3 in tetraethyleneglycol-water mixtures. A mathematical approach based on the tenets of the molecular association theory and a simple lattice model (ASL = association solution + lattice) was used to estimate the solubility values of the investigated porphyrins in water-PEG solutions. The ASL model appeared to present a simple means of estimating the solubility of CoIII5,10,15,20-tetra(4-carboxyphenyl)porphyrin and axial complex with methylimidazole in polyethyleneglycol-water mixtures using a single variable parameter.